2002
DOI: 10.1093/hmg/11.3.273
|View full text |Cite
|
Sign up to set email alerts
|

Reduced fertility and hypersensitivity to mitomycin C characterize Fancg/Xrcc9 null mice

Abstract: Fanconi anemia (FA) is a heterogeneous autosomal recessive chromosomal instability syndrome associated with diverse developmental abnormalities, progressive bone marrow failure and a predisposition to cancer. Spontaneous chromosomal breakage and hypersensitivity to DNA cross-linking agents characterize the cellular FA phenotype. The gene affected in FA complementation group G patients was initially identified as XRCC9, for its ability to partially correct the cellular phenotype of the Chinese hamster ovary (CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
84
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(93 citation statements)
references
References 26 publications
8
84
1
Order By: Relevance
“…We and others have previously created strains of mice with targeted deletions of the murine Fanca, Fancc, and Fancg genes, all components of the FA nuclear complex. These mutants have very similar phenotypes (Chen et al 1996;Whitney et al 1996;Cheng et al 2000;Yang et al 2001;Koomen et al 2002;Noll et al 2002), supporting a model in which the components of the complex participate in a common function. To determine whether Fancd2 participates only in this function in vivo or has additional roles, we generated a strain of mice with a null allele in this gene.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We and others have previously created strains of mice with targeted deletions of the murine Fanca, Fancc, and Fancg genes, all components of the FA nuclear complex. These mutants have very similar phenotypes (Chen et al 1996;Whitney et al 1996;Cheng et al 2000;Yang et al 2001;Koomen et al 2002;Noll et al 2002), supporting a model in which the components of the complex participate in a common function. To determine whether Fancd2 participates only in this function in vivo or has additional roles, we generated a strain of mice with a null allele in this gene.…”
Section: Discussionmentioning
confidence: 76%
“…Knockouts of Fancc (Chen et al 1996;Whitney et al 1996), Fanca (Cheng et al 2000;Noll et al 2002), and Fancg (Yang et al 2001;Koomen et al 2002) all share a defect in germ-cell development and demonstrate cellular sensitivity to agents that produce DNA interstrand cross-links (ICLs). In contrast to human FA patients, however, FA mice do not develop anemia and do not have skeletal defects; nor are they at an increased risk for developing cancer.…”
mentioning
confidence: 99%
“…Patients with FA have immune defi ciencies before bone marrow failure. Pancytopenia typically appears between the ages of 5 and 10, the median age of onset being 7 years old [3]. Clinically, the aff ected FA patient may present with bleeding, pallor and recurrent infections.…”
Section: Introductionmentioning
confidence: 99%
“…Over 100 diff erent mutations have been reported. Six genes FANC have been cloned (FANCA, C, D2, E, F, G) [3,[7][8][9][10]. It would also be interesting to determine whether inherited polymorphisms in Fanconi anemia genes, resulting in more subtle defects in the expression or function of FA proteins, can contribute to an increase in cancer risk [11].…”
Section: Introductionmentioning
confidence: 99%
“…3 Recent experimental studies showed that in animal models of FA, such as Fancg/Xrcc9 null mice or mice mutant for FA complementation group C, the number of germ cells was dramatically reduced, suggesting that FA complementation groups are required for mitotic proliferation of primordial germ cells. [4][5][6] However, the pathophysiology of ovarian failure has not been clearly elucidated in human females and no histo-pathologic study has been published. Causes may be multifactorial, as suggested by some FA patients presenting with hypergonadotropic hypogonadism caused by germ cell insufficiency, with or without associated pituitary stalk interruption.…”
mentioning
confidence: 99%